69 pseudo Elementary Sampling Units (ESUs) set in the Lena Delta derived with expert knowledge - Nele Landgraf; Iuliia Shevtsova; Bringfried Pflug; Birgit Heim (PANGAEA, 2025)
This data set includes training elements representing different vegetation composition in the form of Elementary Sampling Units ESUs: 69 pseudo ESUs set with expert knowledge from the field and from Lena Delta expedition field reports. -The source of the 26 LD18 vegetation plots is Shevtsova et al (2021): Foliage projective cover of 26 vegetation sites of central Lena Delta from 2018. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.935875
In: Landgraf, N et al. (2025): Sentinel-2 derived central Lena Delta land cover classification [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.945057